Extraordinary resources against arbitration decisions in Colombia - Vega Millán, Jesús David (DIXI, 2013)
This paper is the first product of a research project that has as its broader goal to study “The scope and effect of arbitration proceedings since the Constitution of 1991 from jurisprudence and doctrine”. To achieve this goal we have to develop three specific objectives: to know the definition of arbitration and the scope of its competence; to know the grounds for annulment of arbitration decisions; and finally, to present and understand how affirmative action can proceed, opposing the arbiter decision when there are mistakes that he may have made when issuing it.